Usutu virus in cerebrospinal fluid: A 2‐year survey in a Tertiary Care Hospital, Geneva, Switzerland. Issue 3 (9th November 2017) - Cordey, Samuel; Vieille, Gael; Turin, Lara; Kaiser, Laurent
Abstract : In 2009, the Usutu virus (USUV) was first reported as a cause of human neuroinvasive disorders. In Switzerland, USUV has been detected in wild birds with a seroprevalence of up to 6.59% in captive specimens sampled from zoo enclosures. This study investigates the clinical prevalence of USUV in human acute neuroinvasive disorders in Switzerland. Two hundred and fifty‐eight cerebrospinal fluid samples collected between 2015 and 2017 for routine clinical care in a tertiary level hospital (Geneva) were tested for USUV by rRT‐PCR. No samples were found positive, suggesting the absence, or the extremely low circulation of USUV in Western Switzerland.